LEGAL REGULATION OF COMPENSATION FOR DAMAGE WAS CAUSED AS A RESULT OF A TRAFFIC ACCIDENT - Мілімко, Лариса Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to characterize the legal regulation of relations for compensation for damage caused to a legal entity as a result of a traffic accident, identify problems and make suggestions for improving these relations. Methods: the study was conducted using methods such as analysis, synthesis, comparison. Results: the characteristic is given to the legal regulation of relations for compensation for damage caused to a legal entity as a result of a traffic accident, the proposals are formulated to the Law of Ukraine «On compulsory civil liability insurance of owners of land vehicles» and the jurisdiction of disputes for compensation for damage caused to a legal entity is determined as result of a traffic accident. Vehicles are among the sources of increased danger. No one is protected from the negative consequences of these sources, including traffic accidents, and as a result - material and moral damage. However, according to statistics, in 50% of cases the actual perpetrator of the accident does not admit guilt, and in 95% of cases the victim does not compensate the damage voluntarily. In order to guarantee compensation to the injured party, compulsory civil liability insurance has been introduced. Undoubtedly, such insurance has improved the situation in terms of compensation to the victim at the expense of the insurance company. However, not all victims of road accidents receive such compensation and not always such insurance funds are enough to cover the damage. In addition, the issue of damages is complicated in the case when the participants in the accident are vehicles belonging to legal entities. This article is devoted to the problem of compensation of losses to the victim - the legal entity as a result of road accident.